PORTUGUESE INTERNATIONAL PAVILIONS AND NATIONAL STYLE — ARCHITECTURE TENDERS SHAPED BY POLITICAL AND CULTURAL AGENTS - Teresa Neto (Art is on, 2018)
Universal exhibitions were true emblems of modernity in the nineteenth and twentieth centuries, as vehicles of artistic and technical paradigms of each country. Portugal’s participation, from the first Republic to the Estado Novo regime encompass different political and economic circumstances which moulded the strategies to adopt in each participation, and therefore the architectural style that should be used to convey a certain image of the country. The concept of ‘Empire’ dominates the discourse, to be translated into appropriate architectural options of its exhibition pavilions. This sparked a debate between architects and key cultural and political agents, selected as jurors for the architectural tenders held for the Portuguese Pavilions. Evaluating these events means identifying pivotal participants, their proposals and their thoughts on the issue of a representative ʻnational styleʼ. This particular period also dwells with the issue of implementing modern architecture, distanced from eclectic historicisms yet rooted in vernacular elements.